Leveraging Endogenous Dendritic Cells to Enhance the Therapeutic Efficacy of Adoptive T-Cell Therapy and Checkpoint Blockade - Hübbe, Mie Linder; Jæhger, Ditte Elisabeth; Andresen, Thomas Lars; Andersen, Mads Hald (Frontiers in Immunology, 2020)
Adoptive cell therapy (ACT), based on treatment with autologous tumour infiltrating lymphocyte (TIL)-derived or genetically modified chimeric antigen receptor (CAR) T cells, has become a potentially curative therapy for subgroups of patients with melanoma and hematological malignancies. To further improve response rates, and to broaden the applicability of ACT to more types of solid malignancies, it is necessary to explore and define strategies that can be used as adjuvant treatments to ACT. Stimulation of endogenous dendritic cells (DCs) alongside ACT can be used to promote epitope spreading and thereby decrease the risk of tumour escape due to target antigen downregulation, which is a common cause of disease relapse in initially responsive ACT treated patients. Addition of check-point blockade to ACT and DC stimulation might further enhance response rates by counteracting an eventual inactivation of infused and endogenously primed tumour-reactive T cells. This review will outline and discuss therapeutic strategies that can be utilized to engage endogenous DCs alongside ACT and check-point blockade, to strengthen the anti-tumour immune response.